Plant Growth Promotion and Management of Root Knot Nematode Meloidogyne incognita through Glomus aggregatum and Bacillus coagulans and Vermicomposting in Tomato - Serfoji, P (International Journal of Pharmaceutical & Biological Archive, 2013)
Plant Growth Promotion and Management of Root Knot Nematode Meloidogyne incognita through Glomus aggregatum and Bacillus coagulans and Vermicomposting in Tomato